EFISIENSI PENGGUNAAN MODAL TERHADAP PROFITABILITAS PADA PT SARANA SINAR SULAWESI MAKASSAR - Gazali, Agus Umar (FEB Universitas Lakidende, 2020)
The purpose of this research is to know the efficiency of the capital use of PT Sarana Sinar Sulawesi in improving its profitability. The analytical methods used are Weighted Average Cost of Capital (WACC), Leverage and Profitability Ratio Analysis. The results of the analysis show that the use of Capital PT Sarana Sinar Sulawesi has not been efficient in achieving its profitability due to the Weighted Average Cost of Capital of larger companies when compared to Return On Investment, where WACC from year to year is unstable. This is due to the Company's Cost of Debt and Cost of Equity increasing and decreasing eachs. While roi decreased due to decreased Net Profit Margin.